Hayman’s diallel analysis of elite x elite crosses in sesame (Sesamum indicum L.): HAYMAN’S DIALLEL ANALYSIS OF ELITE X ELITE CROSSES IN SESAME - K T RAMYA; C LAVANYA; J JAWAHARLAL; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2021)
The present investigation was carried out to study the genetic components of yield and its ancillary characters in a 8 x 8 full-diallel cross between elite sesame cultivars grown in different geographical regions ofIndia. Hayman’s analysis of variance indicated the presence of both additive and dominance genetic variance for all six characters studied. Ambidirectional dominance wasindicated for all the characters with asymmetrical gene distribution except for seed yield and number of capsules/plant and residual dominance effects for all the characters studied. Branches/plant and test weight indicated epistasis. Seed yield, plant height and oil content showed over dominance while capsules/plant were under partial dominance. Parents viz., HT-1, VRI-3 and TKG-22 had dominant genes with positive effects for seed yield; Phule til, Swetha til and RT-351 for capsule number/plant and crosses between HT-1, TKG-22 and E-8 results in segregants with high oil content. Estimates of components of variance demonstrated the involvement of additive gene effects for seed yield and capsule number, additive and dominant effects for plant height and oil content. Influence of the environment was strong on these characters, which followed simple additive-dominance inheritance.